Evaluating interest rate rules in an estimated DSGE model - Vasco Cúrdia; Andrea Ferrero; Ging Cee Ng; Andrea Tambalotti (Federal Reserve Bank of New York, 2011)
The empirical DSGE (dynamic stochastic general equilibrium) literature pays surprisingly little attention to the behavior of the monetary authority. Alternative policy rule specifications abound, but their relative merit is rarely discussed. We contribute to filling this gap by comparing the fit of a large set of interest rate rules (fifty-five in total), which we estimate within a simple New Keynesian model. We find that specifications in which monetary policy responds to inflation and to deviations of output from its efficient level
Keywords: E48; E58; C11; 330; the one that would prevail in the absence of distortions